2023
DOI: 10.1007/s10911-023-09539-9
|View full text |Cite
|
Sign up to set email alerts
|

PI3K inhibition circumvents resistance to SHP2 blockade in metastatic triple-negative breast cancer

Abstract: The protein tyrosine phosphatase SHP2 activates oncogenic pathways downstream of most receptor tyrosine kinases (RTK) and has been implicated in various cancer types, including the highly aggressive subtype of triple-negative breast cancer (TNBC). Although allosteric inhibitors of SHP2 have been developed and are currently being evaluated in clinical trials, neither the mechanisms of the resistance to these agents, nor the means to circumvent such resistance have been clearly defined. The PI3K signaling pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…Overall, SDUY038 , as a novel SHP2 allosteric inhibitor, exhibited broad antitumor activity against a range of cancer cell lines by downregulating pERK levels and disrupting the MAPK signaling pathway. It is also noteworthy that pAKT was barely detectable with the treatment of 10 μM SDUY038 , which surpasses the effect of 20 μM SHP099 in the MDA-MB-468 cell line, underscoring the potential of the PI3K/AKT signaling pathway in modulating the antiproliferative activity of SDUY038 .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Overall, SDUY038 , as a novel SHP2 allosteric inhibitor, exhibited broad antitumor activity against a range of cancer cell lines by downregulating pERK levels and disrupting the MAPK signaling pathway. It is also noteworthy that pAKT was barely detectable with the treatment of 10 μM SDUY038 , which surpasses the effect of 20 μM SHP099 in the MDA-MB-468 cell line, underscoring the potential of the PI3K/AKT signaling pathway in modulating the antiproliferative activity of SDUY038 .…”
Section: Resultsmentioning
confidence: 95%
“…SHP2 acts as an upstream regulator of cell survival and involves in various crucial signaling cascades, including the RAS/ERK/MAPK and PI3K/AKT signaling pathways. , To investigate the effect of SDUY038 on the phosphorylation level of ERK, Western blotting analysis was performed on a panel of cell lines, including MDA-MB-468, 4T1, SW480, HCT116, RT4 and KYSE520, following the drug treatment (Figure S4). As anticipated, SDUY038 led to a dose-dependent decrease in pERK levels after 24-h treatment, particularly evident in MDA-MB-468 and 4T1 cell lines, which is consistent with its antiproliferative activity.…”
Section: Resultsmentioning
confidence: 99%
“…Consistently, it has also been observed that the coinhibition of SHP2 and PI3K can correct MPD by disrupting p85/SHP2/GAB2 interaction. Moreover, it has been demonstrated that SHP2 also plays a critical role in the development of resistance to PI3K inhibitors, as shown in the preclinical models of metastatic breast cancer where the combination of PI3K and SHP2 inhibition not only results in synergistic tumor growth inhibition but also inhibits metastasis formation ( 44 ). The role of the PI3K/SHP2 axis in the regulation of metastatic progression has also been demonstrated by overexpression experiments in ovarian tumor models ( 45 ).…”
Section: Other Pathways Regulated By Shp2mentioning
confidence: 99%
“…Targeting SHP2 via a selective inhibitor such as SHP099 (35) effectively inhibits the MAPK pathway and counteracts therapeutic resistance when combined with a MEK inhibitor in mutant KRAS-driven cancers (14)(15)(16). While MAPK inhibition via SHP099 in combination with PI3K inhibitors has shown efficacy in other types of cancer (36,37), it remains to be investigated in PDAC. The drug Omipalisib is a potent inhibitor of PI3K complex components p110α/β/δ/γ and downstream factors mTORC1/2, ultimately suppressing activation of AKT (38).…”
Section: Introductionmentioning
confidence: 99%
“…Combined MEK inhibition and PI3K pathway inhibition (via AKT or mTOR) have shown effectiveness in PDAC as well as other cancers (18,26,(39)(40)(41)(42)(43)(44). While MAPK inhibition via SHP099 in combination with PI3K inhibitors has shown efficacy in a few cancers (36,37), it remains to be investigated in PDAC. Omipalisib has been investigated clinically as a single therapeutic agent in solid tumors, but its efficacy was modest, suggesting that further investigation into an optimal combination treatment strategy is needed (45).…”
Section: Introductionmentioning
confidence: 99%